A Proposed Project of Carabao Dung as an Alternative Mosquito Coil: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The study aims to develop an alternative mosquito repellant from carabao dung coupled with extracts of lemongrass and oregano leaves. Some mosquito repellants could include hazardous compounds that cause respiratory problems in humans. In this regard, remember that not everyone can afford to buy mosquito repellents. That is why researchers came up with a single intention. They plan to employ as many natural elements as possible to create this study, such as carabao manure, because it is intended to be low-cost and environmentally beneficial. This study utilized the quantitative-experimental research method while utilizing purposive sampling. The statistical treatment used for this study was a T-test to determine the difference between the assessments of the two groups of respondents.  Using the questionnaire as the research instrument, the researchers surveyed to identify the level of acceptability of carabao dung as an alternative mosquito coil in terms of the construction materials, design and procedure, effectiveness and presentation using statistical analysis. The study's respondents are 10 STEM Students and 5 STEM Teachers. The following procedures were undertaken in developing the model: preparing the carabao dung and all ingredients mixed, moulding it like a coil, and letting it dry using the sun's heat before presenting and testing the product. The result of the study in terms of construction materials, design and procedure, effectiveness, and presentation are highly acceptable. The overall mean of the STEM students is 4.26, interpreted as Highly Acceptable. The overall mean of the STEM teachers is 3.79, interpreted as Highly Acceptable. The t-computed was 2.731, and the t-critical was 2.650, the t-computed > t-critical. It indicates a significant difference between the assessments of the two groups of respondents. The study indicates that using the accurate amount of each ingredient and the right materials can help the product achieve its goals. It also shows that using the right processes and plans can help the project succeed. This study still has some flaws, including methodologies, materials, and designs, which could lead to further research.
Keywords: proposed project; carabao dung as an alternative mosquito coil